Decryption oracle slide attacks on T-310. Issue 3 (4th May 2018) - Courtois, Nicolas
ABSTRACT: T-310 is an important Cold War cipher (Schmeh2006 ). It was the principal encryption algorithm used to protect various state communication lines in Eastern Germany throughout the 1980s. The cipher seems to be quite robust, and until now no researcher has proposed an attack on T-310. This article studies decryption oracle and slide attacks on T-310.